Proteomic Analysis of Mecistocirrus digitatus and Haemonchus contortus Intestinal Protein Extracts and Subsequent Efficacy Testing in a Vaccine Trial - Dicker, Alison J. (Public Library of Science, 2014)
BACKGROUND: Gastrointestinal nematode infections, such as Haemonchus contortus and Mecistocirrus digitatus, are ranked in the top twenty diseases affecting small-holder farmers' livestock, yet research into M. digitatus, which infects cattle and buffalo in Asia is limited. Intestine-derived native protein vaccines are effective against Haemonchus, yet the protective efficacy of intestine-derived M. digitatus proteins has yet to be determined. METHODOLOGY/PRINCIPAL FINDINGS: A simplified protein extraction protocol (A) is described and compared to an established method (B) for protein extraction from H. contortus. Proteomic analysis of the H. contortus and M. digitatus protein extracts identified putative vaccine antigens including aminopeptidases (H11), zinc metallopeptidases, glutamate dehydrogenase, and apical gut membrane polyproteins. A vaccine trial compared the ability of the M. digitatus extract and two different H. contortus extracts to protect sheep against H. contortus challenge. Both Haemonchus fractions (A and B) were highly effective, reducing cumulative Faecal Egg Counts (FEC) by 99.19% and 99.89% and total worm burdens by 87.28% and 93.64% respectively, compared to the unvaccinated controls. There was no effect on H. contortus worm burdens following vaccination with the M. digitatus extract and the 28.2% reduction in cumulative FEC was not statistically significant. However, FEC were consistently lower in the M. digitatus extract vaccinates compared to the un-vaccinated controls from 25 days post-infection. CONCLUSIONS/SIGNIFICANCE: Similar, antigenically cross-reactive proteins are found in H. contortus and M. digitatus; this is the first step towards developing a multivalent native vaccine against Haemonchus species and M. digitatus. The simplified protein extraction method could form the basis for a locally produced vaccine against H. contortus and, possibly M. digitatus, in regions where effective cold chains for vaccine distribution are limited. The application of such a vaccine in these regions would reduce the need for anthelmintic treatment and the resultant selection for anthelmintic resistant parasites.